Anti-phospholipid antibodies as a risk factor for renal injury in patients with systemic lupus erythematosus: a comprehensive analysis - Guan, Hui; Tian, Chengzi; Chen, Lefeng; Wang, Wenjing; Zhang, Lihuan; Huang, Mingcheng; Wang, Xiaofei; Chen, Duo (Frontiers in Immunology, 2026)
BackgroundAlthough the existence of antiphospholipid antibodies (aPL) has been extensively documented as a risk factor for thrombocytopenia, hemolytic anemia, and recurrent miscarriage, their contribution to renal damage in the context of the systemic lupus erythematosus (SLE) is yet to be defined. This meta-analysis investigated the association between aPL and renal injury among patients with SLE.MethodsA systematic literature search was conducted to determine publications that examined the relationship between the level of aPL and renal functioning in SLE patients in four electronic databases (PubMed, Cochrane Library, Embase, and Web of Science). Funnel plots and Egger’s test were utilized to assess the presence of publication bias. Sensitivity analysis and the trim-and-fill method were used in the evaluation of the stability of the results. Subgroup analyses were performed according to study design, geographic region, aPL subtype, publication date, and pathological type of lupus nephritis. Also, the cumulative meta-analyses were conducted by ranking the studies based on the year of publication, sample size, and the Newcastle-Ottawa Scale score.ResultsA total of 34,353 publications were retrieved up to September 12, 2025. After screening, a total of 70 studies (18 case-control, 23 cohort, and 29 cross-sectional) involving 12,456 SLE patients were included. The pooled OR for renal injury in aPL−positive versus aPL−negative patients was 2.09 (1.70–2.58). Subgroup analysis revealed anti-cardiolipin (aCL), lupus anticoagulant (LA), and antiphospholipid syndrome significantly increased the risk of renal injury compared with control groups, 108with OR of 1.71 (1.34–2.18), 2.43 (1.64–3.61), 2.07 (1.48–2.89), respectively. In contrast, no statistically significant increase in renal injury risk was observed in groups positive for anti-β2-glycoprotein I and aPS/PT. Cumulative meta-analyses consistently demonstrated an increased risk of renal injury in aPL-positive patients, and this association remained stable across different publication years, sample sizes, and study quality.ConclusionsSeropositivity for aPL was significantly associated with an increased risk of renal injury in SLE patients, primarily driven by LA and aCL.